The impact of public art education on college students' mental health literacy - Shengyu Zhang; Lege Zhao (Frontiers Media S.A., 2024)
IntroductionThis study aims to explore the impact of public art education on the mental health literacy of College Students.MethodsConducted over a four-month period, the intervention involved freshmen from a Chinese college, comparing 1,334 students in the experimental group with 1,139 in the control group. Data were collected through a self-developed questionnaire and a standardized mental health literacy scale before and after the intervention.ResultsResults showed that the experimental group's overall mental health literacy score significantly increased from 64.051 pre-intervention to 79.260 post-intervention, while the control group showed no significant changes during the same period. The experimental group demonstrated significant improvements in their ability to identify psychological disorders, belief in receiving professional help, attitudes towards seeking appropriate help, and knowledge in seeking mental health information. Furthermore, the frequency of classroom interaction was positively correlated with improvements in mental health literacy (regression coefficient = 2.261***), highlighting the critical role of active participation in public art education settings.ConclusionThis study underscores the importance and effectiveness of implementing public art education in higher education and provides empirical support for future educational policies and practices.